Chronic refractory angina pectoris treated by bilateral stereotactic radiosurgical stellate ganglion ablation: first-in-man case report. Issue 8 (31st August 2021) - Hudec, Miroslav; Jiravsky, Otakar; Spacek, Radim; Neuwirth, Radek; Knybel, Lukas; Sknouril, Libor; Cvek, Jakub; Miklik, Roman
Abstract: Background: Refractory angina pectoris (AP) significantly impairs quality of life in patients with chronic coronary syndrome. Several minimally invasive methods (coronary sinus reducer, cell therapy, laser or shockwave revascularization, and spinal cord stimulation) or non-invasive methods (external counterpulzation) have been studied. However, their routine clinical use has not been widely implemented. Surgical or endoscopic sympathectomy is feasible for permanently relieving angina, but is often contraindicated due to the extent of complications associated with it. Neuromodulation by anaesthetic blockade of the left-sided stellate ganglion (SG) has been shown to relieve angina for days or weeks. To provide a long-term anti-anginal effect, novel pharmacological (phenol-based) or radiofrequency ablation techniques have been individually used to permanently destroy sympathetic pathways. Case summary: We describe a first-in-man use of stereotactic radiosurgical SG ablation using a linear accelerator (CyberKnife) in a heart failure patient after myocardial infarction with chronic refractory AP. Repeated anaesthetic SG blockade in this patient resulted in a significant, but only short-term, clinical improvement. The left, and subsequently the right, SG was ablated by targeted irradiation. During the 1-year follow-up, the patient remained without angina. We did not observe any clinically relevant early or late complications. Atrial fibrillation that developed 2 months after the second procedure was deemed to be associated with a natural progression of co-existing heart failure. Discussion: We conclude that stereotactic radiosurgical SG ablation has the potential to become a minimally invasive and low-risk procedure to treat refractory angina patients. However, this procedure needs to be evaluated in larger patient populations.